Exploring the dynamics of workplace typologies for sex workers in Eastern Ukraine. Issue 9 (2nd September 2022) - Herpai, Nicole; Lazarus, Lisa; Forget, Evelyn; Balakireva, Olga; Pavlova, Daria; McClarty, Leigh; Lorway, Robert; Pickles, Michael; Isac, Shajy; Sandstrom, Paul; Aral, Sevgi; Mishra, Sharmistha; et al.
ABSTRACT: We examine the typologies of workplaces for sex workers in Dnipro, Ukraine as part of the larger Dynamics Study, which explores the influence of conflict on sex work. We conducted a cross-sectional survey with 560 women from September 2017 to October 2018. The results of our study demonstrate a diverse sex work environment with heterogeneity across workplace typologies in terms of remuneration, workload, and safety. Women working in higher prestige typologies earned a higher hourly wage, however client volume also varied which resulted in comparable monthly earnings from sex work across almost all workplace types. While sex workers in Dnipro earn a higher monthly wage than the city mean, they also report experiencing high rates of violence and a lack of personal safety at work. Sex workers in all workplaces, with the exception of those working in art clubs, experienced physical and sexual violence perpetrated by law enforcement officers and sex partners. By understanding more about sex work workplaces, programmes may be better tailored to meet the needs of sex workers and respond to changing work environments due to ongoing conflict and COVID-19 pandemic.